Luteinizing hormone and androstendione are independent predictors of ovulation after laparoscopic ovarian drilling: a retrospective cohort study - Mayerhofer Klaus; Kurz Christine; Nouri Kazem; Wirth Stefan; Ott Johannes; Huber Johannes C; Tempfer Clemens B (BMC, 2009)
Abstract Background Our objective was to investigate luteinizing hormone, follicle-stimulating hormone, testosterone, and androstenedione as predicitve markers for ovulation after laparoscopic ovarian drilling. Methods We retrospectively analyzed 100 clompihen-resistant patients with the polycystic ovary syndrome who underwent laparoscopic ovarian drilling at our department. The main outcome measure was spontaneous postoperative ovulation within three months after laparoscopic ovarian drilling. In order to predict spontaneous ovulation, we tested the following parameters by use of a univariate followed by a multivariate regression model: Preoperative serum levels of LH, FSH, testosterone, and androstenedione as well as patients' age and body mass index. In addition, we focused on pregnancy and life birth rates. Results Spontaneous ovulation was documented in 71/100 patients (71.0%). In a univariate and multivariate analysis, luteinizing hormone (OR 1.58, 95%CI: 1.30-1.92) and androstenedione (OR 3.03, 95%CI: 1.20-7.67), but not follicle-stimulating hormone and testosterone were independent predictors of ovulation. Using a cut-off for luteinizing hormone and androstenedione of 12.1 IU/l and 3.26 ng/ml, respectively, spontaneous ovulation was observed in 63/70 (90.0%) and 36/42 patients (85.7%) with elevated and in 8/30 (26.7%) and 35/58 (60.3%) patients with low luteinizing hormone and androstenedione levels, respectively. The sensitivity, specificity, positive and negatvie predictive values for luteinizing hormone and androstendione as predictors of spontaneous ovulation after ovarian drilling were 88.7% (95%CI: 79.0-95.0%), 75.9% (95%CI: 56.5-89.7%), 90.0% (95%CI: 80.5-95.8%), and 73.3% (95%CI: 54.1-87.7%) for luteinizing hormone, and 50.7% (95%CI: 38.6-62.8%), 79.3% (95%CI: 60.3-92.0%), 85.7% (95%CI: 71.5-94.6%), and 39.7% (95%CI: 27.0-53.4%) for androstenedione, respectively. Complete one-year follow-up was available for 74/100 patients (74%). We observed a one-year pregnancy rate and a resulting life-birth rate of 61% and 51%, respectively. Conclusions Luteinizing hormone and androstenedione prior to laparoscopic ovarian drilling are independent predictors of spontaneous ovulation within three months of surgery. We suggest to preferentially performing laparoscopic ovarian drilling in patients with high luteinizing hormone and androstenedione levels.